Investigating the impact of a novel active gap metering signalization strategy on driver behavior at highway merging sections. (April 2021) - Reinolsmann, Nora; Alhajyaseen, Wael; Brijs, Tom; Pirdavani, Ali; Hussain, Qinaat; Brijs, Kris
Highlights: Active Gap Metering (AGM) can improve driver behavior towards safer operation. A gradual headway increase to the lead vehicle is achieved near on-ramps. Drivers' headway to merging vehicles corresponds to signalized safety distance. Critical minimum time-to-collision (<1.5 s) to the merging vehicle is eliminated. Combined AGM application with variable speed limits (VSL) is also effective. Abstract: A safe headway to the lead vehicle is important to reduce conflicts with merging vehicles from highway on-ramps. Previous research has outlined the advantage of gap metering strategies to yield sufficient space to merging vehicles and improve highway capacity during peak hours. However, prevailing gap metering systems fail to indicate the minimum required gap and leave it to the drivers' judgment to adjust their headway. This paper proposes a new Active Gap Metering (AGM) signalization that helps outer lane drivers to adjust their headway to the lead vehicle when approaching highway ramps with incoming vehicles. This AGM signalization represents a combination of pavement markings and an innovative Variable Message Sign (VMS). The AGM system was tested alone and in combination with additional variable speed limits (VSL) in distinct environments of the Doha Expressway in the State of Qatar using a driving simulator. The driving behavior of 64 drivers was analyzed using repeated-measures ANOVA. The results showed that the AGM effectively influenced the drivers' behavior on the right stream lane. Drivers did gradually increase the distance to the lead vehicle, which resulted in optimal headways to merging on-ramp vehicles. Most importantly, the minimum time-to-collision (TTCmin ) to the merging vehicle was increased by an additional 1–1.5 s as compared to no treatment. The proposed AGM signalization can, therefore, be considered by policymakers to influence drivers' headways at critical merging sections.